2017
DOI: 10.1007/s11751-017-0301-y
|View full text |Cite
|
Sign up to set email alerts
|

Complex tibial fractures are associated with lower social classes and predict early exit from employment and worse patient-reported QOL: a prospective observational study of 46 complex tibial fractures treated with a ring fixator

Abstract: The long-term outcomes following complex fractures of the tibia are reported to carry a risk of knee pain, malalignment, articular injury and post-traumatic osteoarthritis. The main objective of this study was to account for the patient-reported quality of life (QOL) 12 months after ring fixator removal in patients with a complex tibial fracture. Secondary objectives included a review of the socio-economic characteristics of the patient group and the rate of return to work in the study period. A prospective fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This is partly due to it being an uncommon, complex articular surface injury with very heterogenic fracture morphology and a high rate of accompanying soft tissue injuries, such as compartment syndrome and vascular, chondral, ligament and meniscal lesions [ 3 6 ]. Moreover, despite advances in diagnostics and surgical methods, high rates of posttraumatic osteoarthritis up to 40% [ 7 ] and large proportions with poor outcomes still remain [ 8 ], which could be due to an incongruent restoration after osteosynthesis. This is particular important since optimum restoration of the joint surface and articular congruity seems to be decisive for achieving satisfactory clinical results [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is partly due to it being an uncommon, complex articular surface injury with very heterogenic fracture morphology and a high rate of accompanying soft tissue injuries, such as compartment syndrome and vascular, chondral, ligament and meniscal lesions [ 3 6 ]. Moreover, despite advances in diagnostics and surgical methods, high rates of posttraumatic osteoarthritis up to 40% [ 7 ] and large proportions with poor outcomes still remain [ 8 ], which could be due to an incongruent restoration after osteosynthesis. This is particular important since optimum restoration of the joint surface and articular congruity seems to be decisive for achieving satisfactory clinical results [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over 66% of patients felt that this injury was still affecting their lifestyle, despite the fact that the mean time of review after the injury was 4.6 years. Elsoe et al found that only 27% of patients with tibial fractures had returned to employment 18 months after injury [ 10 ]. Volgas et al reported that 37% of patients had to sell possessions to meet financial obligations after their injuries [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2] Operative treatment is dependent on the severity of the fracture and can include internal and/or external fixation and staged treatment plans in fractures where there is significant deformity. [3] The preferred operative treatment is intramedullary nailing [4] where osseous union, length, and alignment are reproducibly able to be achieved. [5] Tibial fractures are quite painful, but ineffective coping strategies and pain medication regimens can make the pain much more severe for the patient.…”
Section: Introductionmentioning
confidence: 99%